Photography and interpretations of the word: art and education - Lucinea Aparecida de Rezende; Sandra Aparecida Pires Franco; Letícia Marquez (Discursos Fotográficos, 2013)
This paper analyzes images made and broadcasted by Foto Clube de Londrina (Londrina’s Photo Club) in 2011. We aim to think over the imagery reading, specially photograph, at education scope. To achieve this target, we understood photography as something possible to be interpretated and also as a work of art. This way, we show that readers can be benefited by reading and rereading photographs, when they are seen along with the words reading.